On Distance Function in Some New Analytic Bergman Type Spaces in ℂn. (6th May 2014) - Shamoyan, Romi F.; Mihić, Olivera R.
Abstract : We extend our previous sharp results on distances obtained for analytic Bergman type spaces in unit disk to some new analytic Bergman type spaces in higher dimensions inℂ n . Also, we study the same problem in anisotropic mixed normh ( p, q, s ) spaces consisting ofn -harmonic functions on the unit polydisc ofℂ n .